Concept of Anti-Bullying Character Education Development through Pancasila Student Profile Strengthening Project (P5) in Elementary School: Konsep Pengembangan Pendidikan Karakter Anti-Bulying Melalui Project Penguatan Profil Pelajar Pancasila (P5) di MI/SD - Uswatun Hasanah; Sholeh; Nidzom Muis (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2023)
This study aims to determine the concept of anti-bullying character education development through the Pancasila Student Profile Enhancement Project (P5) at MI/SD. This research method uses library research (library research). Data collection techniques through data searches, related documents, books, articles and other documents. The data source consists of primary and secondary data. The results of this study show that the concept of developing a student profile can develop an anti-bullying character by adopting six main characteristics in the student profile: 1) belief and fear of the god of YME, as well as noble morality; 2) global self-righteousness; 3) gotong-royong; 4) self-sufficiency; 5) criticism; and 6) creativity. Through the development of anti-bullying character education based on the project of strengthening the profile of students Pancasila can prevent the occurrence of cases of bullying in schools so that the learning objectives are achieved, can improve the quality of self or moral, educational, and social elements in schools, the academic quality of students can qualify, and open up opportunities for self-development in a generation valuable to him, his family, community, nation, and country. Abstrak Penelitian ini bertujuan untuk mengetahui konsep pengembangan pendidikan karakter anti-bullying melalui Proyek Penguatan Profil Pelajar Pancasila (P5) di MI/SD. Metode penelitian ini menggunakan penelitian kepustakaan (library research). Teknik pengumpulan data melalui pencarian data, dokumen terkait, buku, artikel, dan dokumen lainnya. Sumber data terdiri data primer dan sekunder. Hasil penelitian ini menunjukkan bahwa konsep pengembangan profil pelajar pancasila dapat mengembangkan karakter anti-bullying dengan mengadopsi enam karakteristik utama dalam profil pelajar pancasila yaitu: 1) beriman dan bertakwa kepada tuhan YME, serta berakhlak mulia; 2) berkebinekaan global; 3) gotong-royong; 4) mandiri; 5) bernalar kritis; dan 6) kreatif. Melalui pengembangan pendidikan karakter anti-bullying berdasarkan proyek penguatan profil pelajar pancasila dapat mencegah terjadinya kasus bullying di sekolah sehingga tujuan pembelajaran tercapai, dapat meningkatkan kualitas diri atau unsur moral, pendidikan dan sosial di sekolah, mutu akademik peserta didik dapat berkualitas, dan membuka peluang pengembangan diri menjadi generasi yang berharga bagi dirinya, keluarga, masyarakat, bangsa dan negara.